2020
DOI: 10.3389/fnins.2019.01390
|View full text |Cite
|
Sign up to set email alerts
|

RNA Editing of Serotonin 2C Receptor and Alcohol Intake

Abstract: Serotonin 2C receptor (5-HT 2C R) belongs to the superfamily of seven transmembrane domain receptors coupled to G proteins (GPCR). It is broadly distributed in the CNS and its expression is relatively high in the limbic system including the amygdala, nucleus accumbens (NAc), hippocampus, and hypothalamus. Based on its expression patterns and numerous pharmacological studies, 5-HT 2C R is thought to be involved in various brain functions including emotion, appetite, and motor behavior. Here, we review 5-HT 2C R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 76 publications
0
7
0
Order By: Relevance
“…Additionally, it is well accepted that mRNA levels do not necessarily reflect levels of translated protein, and protein localization and activity may also impact function/signaling without altering mRNA levels. Furthermore, there is growing evidence that Htr2c undergoes RNA editing in neuropsychiatric disease, such as PTSD (Baratta et al, 2016), and such Htr2c alternative splicing can cause the resulting 5-HT2C isoform to be constitutively active in the absence of ligands (Tanaka and Watanabe, 2019). Chronic ethanol vapor exposure in mice (C57BL6) also increases levels of edited isoforms of Htr2c mRNA (Watanabe et al, 2014) in the nucleus accumbens, which is associated with increased ethanol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it is well accepted that mRNA levels do not necessarily reflect levels of translated protein, and protein localization and activity may also impact function/signaling without altering mRNA levels. Furthermore, there is growing evidence that Htr2c undergoes RNA editing in neuropsychiatric disease, such as PTSD (Baratta et al, 2016), and such Htr2c alternative splicing can cause the resulting 5-HT2C isoform to be constitutively active in the absence of ligands (Tanaka and Watanabe, 2019). Chronic ethanol vapor exposure in mice (C57BL6) also increases levels of edited isoforms of Htr2c mRNA (Watanabe et al, 2014) in the nucleus accumbens, which is associated with increased ethanol drinking.…”
Section: Discussionmentioning
confidence: 99%
“…In the ventral hippocampus, HTR1A, 2A, 2C, and 7 play a role in mood- and anxiety-related behavior and are involved in the antidepressant effects of SSRIs. Expression of the 5-HT2C receptor in mice modulated alcohol intake, which may be relevant to human alcoholism [ 103 ]. Increased cortical expression of 5-HT2CR mRNA had previously been found in major depressive suicide victims [ 104 ].…”
Section: Discussionmentioning
confidence: 99%
“…Comprehensive studies on alterations in RNA editing have demonstrated changes in editing efficiencies at many editing sites in the brains of patients with autism spectrum disorder, a common neurodevelopmental disorder characterized by social communication deficits and repetitive sensorimotor behaviors [102]; however, no specific editing site relevant to the pathogenesis could be identified [69,103]. In addition, studies in mice and rats have shown negative effects of alcohol and/or cocaine abuse/abstinence on the RNA editing efficiency of ADAR2 [104,105].…”
Section: Rna Editing and Neurological Diseasesmentioning
confidence: 99%